Welche Bedeutung haben physische Leistungssteigerungen, Alter, Geschlecht und Trainingsumfang für die Wirksamkeit eines Rückentrainings? = What influence do increased physical performance, age, sex and training frequency have on the effectiveness of back training? - Müller, Gerhard; Bombana, Manuela; Lyssenko, Lisa (Der Schmerz, 2019)
BackgroundActive exercising can effectively reduce low back pain but the mechanisms of action are still unclear.ObjectiveWhat are the influences of training frequency, increased physical performance, age and gender on the effectiveness of a multimodal back training?Material and methodsA total of 1395 persons with back pain (mean age 46.9 ± 12.3 years, 65% female) took part in a multimodal back training over 24 months in the context of a multicenter study (39 locations). Back pain, physical capacity of strength, mobility and bilateral strength ratio of the spine stabilizing muscles were measured at the beginning of the training and after 6, 12 and 18 months.Results and discussionThe participants trained on average for 41.0 (SD ± 17.8) 60-min training units. This resulted in an increase of strength (28.1%), mobility (14.7%) and strength ratio (6.5%) compared to an age and gender-matched cohort without back pain. Back pain was reduced by 37.5%. The reduction in back pain can be ascribed to the training frequency by 70% and to increased physical performance by 30%. Age only marginally influenced the effect of training, while gender had no significant effect.ConclusionIncreases in physical performance have positive effects on the reduction of back pain but the number of training sessions was shown to be more relevant in the reduction of low back pain.
Gesehen am 11.06.2019